Business Feasibility Test and Community-Based Waste Management Model in Kutasari Village, Banyumas District : Uji Kelayakan Bisnis dan Model Pengelolaan Sampah Berbasis Masyarakat di Desa Kutasari, Kabupaten Banyumas - Herlina, Dian Nora; Wahyuni, Yulina Tri; Santi; Anisa, Faefaya Ziadatul; Purnomo, Sodik Dwi; Retnowati, Diah (Procedia of Social Sciences and Humanities, 2022)
The rate of population growth that increases every year is accompanied by the level of public consumption, which can trigger an increase in waste production which impacts the community. Therefore, the research objectives were 1) to identify the potential for waste management in Kutasari Village, Baturaden District Banyumas Regency; 2) analyze the business feasibility of a waste in Kutasari Village, Baturaden District Banyumas Regency from a financial perspective; 3) identify the driving and inhibiting factors in waste bank management management in Kutasari Village, Baturaden District Banyumas Regency; 4) identify stakeholders involved in waste bank management management in Kutasari Village, Baturaden District Banyumas Regency, and 5) formulate a waste bank management model management in Kutasari Village, Baturaden District Banyumas Regency. The research method was a mixed-method of the business feasibility method and the Miles and Huberman method. Furthermore, the determination of research location used the purposive sampling technique. The results showed that the waste bank was an alternative solution in waste management. Financially, this business was feasible to run. It could be seen from the R/C ratio value, which was 1.41. The driving factor in the management of waste banks was public awareness of the economic value of waste. In contrast, the inhibiting factor was the lack of community participation in innovation. Stakeholders involved in waste bank management were local governments, private institutions, universities, collectors, and the community. Then the formation of a waste management model is expected to improve the community's economy. In addition, this model sought to empower the community to increase household income sustainably.